In vitro study reveals antimicrobial activity of essential oils against Klebsiella pneumoniae isolates from Nile tilapia - D. Vaneci-Silva; R. Nakamura-Silva; M. Oliveira-Silva; A. Pitondo-Silva; I. M. Assane; F. Pilarski (Brazilian Journal of Biology)
Abstract Recent studies have shown a growing presence of Klebsiella pneumoniae in aquatic environments, raising concerns for fish production due to its resistance to many antimicrobials. This bacterium is commonly associated with urinary tract infections, pneumonia, and septicemia in humans. Controlling bacterial infectious diseases in fish is a significant challenge in aquaculture. In Brazil, only florfenicol and oxytetracycline are approved for use in this sector. Therefore, in this study, we assessed the in vitro antibacterial impact and hemolytic activity of 16 essential oils (EOs) and two frequently used antimicrobial agents in aquaculture (florfenicol and oxytetracycline) against seven strains of K. pneumoniae isolated from Nile tilapia. The EOs were characterized chemically using gas chromatography with a flame ionization detector and verified with mass spectrometry. The microdilution technique using 96-well plates was employed to evaluate the minimum inhibitory concentration (MIC), ranging from 0.078125 to 20 µg mL-1 for essential oils (EOs) and from 0.0075 a 64 µg mL-1 for antimicrobials. To determine the minimum bactericidal concentration (MBC), 10 µL aliquots from wells that did not show growth in the MIC tests were cultured on Petri dishes containing Muller Hinton Agar. The hemolytic activity of the EOs was evaluated using an erythrocyte lysis assay. The primary components of Thymus vulgaris were thymol (53.3%) and p-cymene (20.8%), while those of Melaleuca alternifolia were 1-terpinen-4-ol (40.5%), γ-terpinene (19.7%), and α-terpinene (1.6%). Significant hemolytic activity was only observed in M. alternifolia tests (>33% lysis). T. vulgaris EO exhibited the highest activity against K. pneumoniae strains, while M. alternifolia EO demonstrated MIC and MBC against all strains. EOs from Corymbia citriodora, Artemisia vulgaris, Citrus bergamia, Cananga odorata, Boswellia carterii, and Pelargonium peltatum also yielded positive results. All strains were resistant to the tested antimicrobial agents. Based on these findings, T. vulgaris was the most promising EO for treating K. pneumoniae in fish.